18F-Labeled o‑aminopyridyl alkynyl radioligands targeting colony-stimulating factor 1 receptor for neuroinflammation imaging. (1st April 2023) - An, Xiaodan; Wang, Jingqi; Tong, Linjiang; Zhang, Xiaojun; Fu, Hualong; Zhang, Jinming; Xie, Hua; Huang, Yiyun; Jia, Hongmei
Graphical abstract: Abstract: We report the design, synthesis and evaluation of five o ‑aminopyridyl alkynyl derivatives as colony-stimulating factor 1 receptor (CSF-1R) ligands. Compounds 4 and 5 with the fluoroethoxy group at the meta - or para -position of the phenyl ring possessed nanomolar inhibitory potency against CSF-1R with IC50 values of 7.6 nM and 2.3 nM, respectively. Radioligands [ 18 F]4 and [ 18 F]5 were obtained in radiochemical yields of 17.2 ± 5.3% (n = 5, decay-corrected) and 14.0 ± 4.3% (n = 4, decay-corrected), with radiochemical purity of > 99% and molar activity of 9–12 GBq/μmol (n = 5) and 6–8 GBq/μmol (n = 4), respectively. In biodistribution studies, radioligands [ 18 F]4 and [ 18 F]5 showed moderate brain uptake in male ICR mice with 1.52 ± 0.15 and 0.91 ± 0.07% ID/g, respectively, at 15 min. Metabolic stability studies in mouse brain revealed that [ 18 F]4 exhibited high stability while [ 18 F]5 suffered from low stability. Higher accumulation of [ 18 F]4 in the brain of lipopolysaccharide (LPS)-treated mice was observed, and further pretreatment of BLZ945 or CPPC led to remarkable reduction, indicating specific binding of [ 18 F]4 to CSF-1R.